Preliminary checklist of non-agaricoid macromycetes in the Korup National Park, Cameroon and surrounding area - Hjortstam, K.; Ryvarden, L.; Watling, R. (Edinburgh Journal of Botany, 2010)
The identifications of taxa of larger fungi (basidiomycetes) covering collections from the Korup National Park, Cameroon is given with relevant details on the distribution elsewhere in the world if known. A few other records from the south western province are also given. Several rare and previously unrecorded fungi for the area are documented.